2021
DOI: 10.3389/fnhum.2021.612345
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in Accessing Vowel Representations Are Driven by Phonological and Acoustic Properties: Neural and Behavioral Evidence From Natural German Minimal Pairs

Abstract: In vowel discrimination, commonly found discrimination patterns are directional asymmetries where discrimination is faster (or easier) if differing vowels are presented in a certain sequence compared to the reversed sequence. Different models of speech sound processing try to account for these asymmetries based on either phonetic or phonological properties. In this study, we tested and compared two of those often-discussed models, namely the Featurally Underspecified Lexicon (FUL) model (Lahiri and Reetz, 2002… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 99 publications
(51 reference statements)
0
2
0
1
Order By: Relevance
“…Perceptual asymmetries have also been observed in vowel perception, with discrimination performance depending on the order in which the stimuli are presented. Several behavioral studies have shown that is easier to discriminate contrasts that move from more central to more peripheral, and thus more acoustically focal, regions of the vowel space than when the same stimuli are presented in the opposite direction (Masapollo et al, 2017;Polka & Bohn, 2003; however, neurophysiological evidence for these asymmetries is less robust (de Rue et al, 2021;Polka et al, 2021;Riedinger et al, 2021). In addition to vowel peripherality and focality, prototypicality and frequency also result in perceptual asymmetries (Kuhl et al, 1992(Kuhl et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Perceptual asymmetries have also been observed in vowel perception, with discrimination performance depending on the order in which the stimuli are presented. Several behavioral studies have shown that is easier to discriminate contrasts that move from more central to more peripheral, and thus more acoustically focal, regions of the vowel space than when the same stimuli are presented in the opposite direction (Masapollo et al, 2017;Polka & Bohn, 2003; however, neurophysiological evidence for these asymmetries is less robust (de Rue et al, 2021;Polka et al, 2021;Riedinger et al, 2021). In addition to vowel peripherality and focality, prototypicality and frequency also result in perceptual asymmetries (Kuhl et al, 1992(Kuhl et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Perceptual asymmetries have also been observed in vowel perception, with discrimination performance depending on the order in which the stimuli are presented. Several behavioural studies have shown that is easier to discriminate contrasts that move from more central to more peripheral, and thus more acoustically focal, regions of the vowel space than when the same stimuli are presented in the opposite direction (Masapollo et al, 2017;Polka & Bohn, 2003; however, neurophysiological evidence for these asymmetries is less robust (de Rue et al, 2021;Polka et al, 2021;Riedinger et al, 2021). In addition to vowel peripherality and focality, prototypicality and frequency also result in perceptual asymmetries (Kuhl et al, 1992(Kuhl et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…pelanggaran sintaksis pada bahasa ibu (Hanna et al, 2017;Pulvermüller & Shtyrov, 2003;Pulvermüller et al, 2008), kandungan semantik emosional (Zora et al, 2020), efek pelatihan bahasa (Aleksandrov et al, 2019), serta informasi prosodi seperti penekanan nada suara komparatif baik antar bahasa (Garami et al, 2017;Honbolygó et al, 2020) maupun aksen regional (Brunellière et al, 2011). Penelitian mengenai representasi fonemik (Cummings et al, 2021;Riedinger et al, 2021) menemukan adanya asimetris MMN di mana beberapa suara ucap menimbulkan MMN sementara suara lain tidak.…”
Section: Aplikasi Dan Potensi Penelitian Mmnunclassified